Book Review: Stephen Ison and Tom Rye (eds.): The Implementation and Effectiveness of Transport Demand Management Measures; an International Perspective - Heijden, Rob van der (European Journal of Transport and Infrastructure Research, 2010)
The growing difficulties with managing congestion in road traffic have steadily increased attention for transport management approaches that focus on reducing the need for travelling and switching modes to alternative mobility options. The set of measures available to transport professionals for bringing about such a change in travel behaviour constitutes the domain of Transport Demand Management (TDM). This book deals with TDM, in particular those measures that associate with commuting-induced road congestion. “The book seeks to review the nature of particular TDM measures, their effectiveness and issues relating to implementation and how the barriers to the implementation of the respective measures may be overcome” (p. 2). Especially the special attention for issues of implementation is interesting, since all too often transport planners tend to mainly emphasize effectiveness of interventions in the transport system, while neglecting the difficulties involved with bringing proposed interventions to reality.